ANALISIS DAMPAK PEMASARAN MEDIA SOSIAL, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN - Caroline, Susan Melanie Patricia; Wulandari, Jeni; Roni, May (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
This study examines the influence of social media marketing, brand image, and product quality on purchasing decisions for Luxcrime beauty products. The approach used is quantitative with explanatory research methods. The population in this study were TikTok Luxcrime followers with a sample size of 100 respondents who were taken using Convenience sampling technique. The sampling process used a questionnaire with a Likert scale. Data analysis in this study used multiple linear analysis with the help of the SPSS 25.0 application. Based on the research results, social media marketing partially affects purchasing decisions, while brand image partially has no effect on purchasing decisions, and product quality partially affects purchasing decisions. Meanwhile, simultaneously there is an influence between all variables.